Effect of Physical Activity on Blood Pressure Distribution among School Children - Anisa M. Durrani; Waseem Fatima (Advances in Public Health)
The present study analyzed the relationship between physical activity and blood pressure in 701 school children aged 12–16 years (girls = 338, boys = 363). During the baseline examination, systolic blood pressure (SBP) and diastolic blood pressure (DBP), height, weight, and 24-hour recall of the working day activity with duration were recorded. Total activity score and type of activity were calculated by weighing the activity level. Mean, standard deviation, and correlation coefficient were calculated by using SPSS 12.0 version. The results revealed that rise in blood pressure was directly proportional to the increase in age. The range of systolic blood pressure was found to be high in low risk blood pressure (LBP) group than in elevated blood pressure (EBP) group showing direct association of activity level and systolic blood pressure. Physical activity score was found to be more in LBP group than in EBP group. Our results support the hypothesis that SBP is independently related to the level of habitual physical activity in children.